The Effects of Overweight and Obesity on Depression, Anxiety and Bullying among Adolescent Females - Erna Ýr Styrkársdóttir 1989- (2014)
Rates of overweight and obesity among adolescents has increased over the years, bullying has also been increasing. Research has differed on the association between overweight and obesity among adolescents and depression symptoms while research have found an association between overweight and obesity and anxiety symptoms among adolescents. It has been shown that the experience of being bullied increased the risk of depression and anxiety. In this current study the effects of overweight and obesity among adolescent females and their symptoms of depression, anxiety and their experience of being bullied was investigated. The relationship between bullying and symptoms of depression and anxiety was also examined. Finally it was examined whether bullying moderated the effects of overweight and obesity on depression and anxiety symptoms. The Icelandic Centre for Social Research and Analysis collected data for this study as a part of their research “Youth in Iceland 2007”. Participants were 2,115 adolescent females in the ages of 16 to19 years. The results showed that overweight and obesity was associated with symptoms of depression, the experience of being bullied was associated with symptoms of depression and anxiety. The results also showed that there was not a significant interaction between overweight and obesity and bullying experience. Key words: overweight, obesity, depression, anxiety, bullying Algengi ofþyndar og offitu meðal ungmenna hefur aukist á síðustu árum. Einnig hefur einelti verið að aukast. Niðurstöður rannsókna sem skoðað hafa áhrif ofþyngdar og offitu meðal ungmenna hafa verið misvísandi á meðan sýnt hefur verið fram á tengsl milli ofþyngdar og offitu meðal ungmenna og kvíða. Einnig hefur verið sýnt fram á það að einstaklingar sem verða fyrir einelti upplifi frekar kvíða og þunglyndi heldur en þeir einstaklingar sem ekki verða fyrir einelti. Í þessari rannsókn voru áhrif ofþyngdar og offitu meðal unglingsstúlkna á einkenni kvíða, þunglyndis og reynslu af einelti könnuð. Einnig var sambandið á ...